2015
DOI: 10.1016/j.tjog.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 E6 modulates the expression of host microRNAs in cervical cancer

Abstract: Our results indicate that HPV infection and subsequent transformation take place through complex regulatory patterns of gene expression in the host cells, part of which are regulated by the E6 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…There is evidence that HPV alters the expression of host cell microRNAs and the cargo of EVs released by cervical cancer cells . However, despite the common viral aetiology, there are no similar studies in OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that HPV alters the expression of host cell microRNAs and the cargo of EVs released by cervical cancer cells . However, despite the common viral aetiology, there are no similar studies in OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also demonstrated that the expression of miR-218 was strongly downregulated by HPV E6 [14, 20], but the mechanisms of the function of HPV on miR-218 and the role of miR-218 on the metastasis of cervical cancer are not well understood. In the present study, we attempted to further explore the role of miR-218 on the metastasis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms that regulate the spread of HPV + HNSCC remain to be explored, E6 and E7 have also been shown to increase the migration of cervical cancer cells which is thought to occur by decreasing RhoA activity . Rho GTPases are overexpressed in HNSCC, and RhoA controls actomyosin contractility to mediate cell migration .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RhoA signaling can promote invadopodia activity . While E6 can deregulate miRNA expression to affect migration, these mechanisms are mediated by p53 which is inactivated in SCC‐25 cells . Therefore, HPV may exert its effects on Rho through additional mechanisms which alter downstream signaling important for migration and invadopodia activity.…”
Section: Discussionmentioning
confidence: 99%